CHANGES IN INSTRUMENTAL AND SENSORY CHARACTERISTICS OF TILAPIA FISH STEAKS DURING COLD BLANCHING AND COOKING TREATMENTS - K. DHANAPAL,; G.V.S. REDDY,; B.B. NAYAK,; G. VENKATESHWARLU,; A. BALASUBRAMANIAN,; REDDY, A. DEVIVARAPRASAD; S. BASU, (The Bioscan, 2013)
Color and texture of the food are considered as the prime qualities evaluated by the consumers either by perception or consumption. The present study was conducted to find out the changes in color and texture of tilapia meat while cold blanched with the 5% salt solution, 10% salt solution and 15% salt solution for 30, 60 and 90 minutes respectively followed by steam cooking at different time intervals such as 1, 2, 3, 4, 5, 6 and 7 minutes. The samples were analyzed for color characteristics like lightness (L*), redness (a*), yellowishness (b*), Hue color and saturation index. Besides, textural characteristics like hardness, adhesiveness, resilience and stringiness and sensory characteristics of fish meat were analyzed. The a* value and hue color turned from negative to positive value at the fifth minute of cooking. L*, b* and saturation index values increased little up to fifth minutes and later the values were retained. 5 minutes steam cooking yielded good textural parameters than other cooking periods. The fish steaks dipped for 60 min in 10% salt concentration and 5 minutes steam cooked exhibited the excellent color and textural characteristics. Under this process, obtained color values such as L*, a*, b*, Hue angle and Saturation index were 70.64±1.20, -1.19±0.62, 12.20±0.36, -16.74±17 and 12.27±0.36 respectively and the textural characteristics of Hardness (gf), Adhesiveness (gs), Stringiness (mm) and Resilience were 82.10±27.27, -13.10±2.27, 9.23±0.06 and 0.24±0.29 respectively. The study revealed that the cooked products had good consumer acceptance.